KOMPARASI KREDIBILITAS PENYELENGGARAAN UNBK DAN UNKP PADA PELAJARAN MATEMATIKA - Kusaeri Kusaeri; A. Saepul Hamdani; Suparto Suparto; Elmita Irmanila (Jurnal Ilmu Pendidikan, 2018)
Abstract: Administration Credibility of the Computer-based and the Paper-and-pencil National Examination in Mathematics Subject. This survey compares the administration credibility between computer-based and paper-and-pencil national examination of one subject, that is, mathematics. The credibility was measured from the perspectives of RAVEN – reputation, ability to observe, vested interest, expertise, and neutrality. Three schools in Pasuruan regency were selected to represent the computer-based, and another three to represent the paper-and-pencil test. The data were collected after the 2017 national examination using questionnaires and interview guide. The questionnaires were distributed to the students and mathematics teachers, whereas the interviews were carried out with the headmasters. The results of data analysis reveal that the computer-based final exam have better credibility in the areas of ability to observe and expertise, while the paper-and-pencil one in reputation and neutrality. In terms of vested interest, the two types of test do not differ.Abstrak: Komparasi Kredibilitas Penyelenggaraan UNBK dan UNKP pada Pelajaran Matematika. Penelitian ini bertujuan membandingkan kredibilitas penyelenggaraan UNBK dan UNKP yang berfokus pada mata pelajaran matematika. Kredibilitas UN dalam penelitian ini dilihat dari aspek reputation, ability to observe, vested interest, expertise, dan neutrality atau RAVEN. Penelitian ini termasuk dalam kategori penelitian survei, dilakukan di Kabupaten Pasuruan pada Bulan April - Mei 2017 (setelah diselenggarakannya UN 2017). Sampel penelitian yakni 3 sekolah penyelenggara UNBK dan 3 sekolah penyelenggara UNKP dengan menggunakan teknik pengumpulan data berupa kuesioner dan wawancara. Kuesioner diberikan kepada siswa dan guru matematika sedangkan wawancara dilakukan pada kepala sekolah. Hasil penelitian menunjukkan bahwa UNBK unggul pada aspek ability to observe dan expertise, sedangkan UNKP unggul pada aspek reputation dan neutrality. Pada aspek vested interest, perbandingan antara UNBK dan UNKP adalah sama.